2014
DOI: 10.1128/mcb.00360-13
|View full text |Cite
|
Sign up to set email alerts
|

DREAM Controls the On/Off Switch of Specific Activity-Dependent Transcription Pathways

Abstract: h Changes in nuclear Ca 2؉ homeostasis activate specific gene expression programs and are central to the acquisition and storage of information in the brain. DREAM (downstream regulatory element antagonist modulator), also known as calsenilin/KChIP-3 (K ؉ channel interacting protein 3), is a Ca 2؉ -binding protein that binds DNA and represses transcription in a Ca 2؉ -dependent manner. To study the function of DREAM in the brain, we used transgenic mice expressing a Ca 2؉ -insensitive/CREB-independent dominant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 55 publications
0
55
0
Order By: Relevance
“…Although the exact details of this pathway are yet to be determined, DREAM might serve as a DG-specific regulator for Ca 2+ signalling to CREB-CBP complex formation. Consistent with this idea, DREAM knockouts show enhanced contextual fear memory (Alexander et al, 2009), and transgenic mice expressing a dominant active DREAM (daDREAM) showed strong deficits in watermaze, a spatial memory task and slight deficit in active avoidance test, all of which involves the hippocampus (Mellstrom et al, 2014). In keeping with evidence that Npas4 and BDNF are regulated by DREAM, daDREAM transgenic mice showed downregulation of GABAergic synapses and enhanced LTP in DG (Mellstrom et al, 2014).…”
Section: A Critical Role For Srf In Circuit Rewiring and Plasticitymentioning
confidence: 61%
“…Although the exact details of this pathway are yet to be determined, DREAM might serve as a DG-specific regulator for Ca 2+ signalling to CREB-CBP complex formation. Consistent with this idea, DREAM knockouts show enhanced contextual fear memory (Alexander et al, 2009), and transgenic mice expressing a dominant active DREAM (daDREAM) showed strong deficits in watermaze, a spatial memory task and slight deficit in active avoidance test, all of which involves the hippocampus (Mellstrom et al, 2014). In keeping with evidence that Npas4 and BDNF are regulated by DREAM, daDREAM transgenic mice showed downregulation of GABAergic synapses and enhanced LTP in DG (Mellstrom et al, 2014).…”
Section: A Critical Role For Srf In Circuit Rewiring and Plasticitymentioning
confidence: 61%
“…Likewise, the A-type K + channel subunit KChip3 (a member of the NCS-1 like Ca 2+ binding protein family) is known as the transcriptional repressor DREAM (Jo et al 2001;Buxbaum 2004), and can shuttle from the membrane to the nucleus in inverse correlation with cellular Ca 2+ levels (Fig. 1) (Li and Adelman 2000;Sours-Brothers et al 2009;Mellstrom et al 2014).…”
Section: Cav13 L-type Ca 2+ Channels Stabilize and Stimulate Activitmentioning
confidence: 99%
“…The first EF-hand domain was functionally dead due to the presence of a CPXG motif that prevents Ca 2+ binding (15). Upon an increase in intracellular Ca 2+ , the DREAM tetramer binds Ca 2+ (15, 16), is dissociated from DNA without disruping the tetrameric structure (17), and is exported out of the nucleus to the cytoplasm as dimers, thereby allowing gene transcription (Figure 1) (18). The DRE sequence is observed in multiple genes, including PDYN (prodynorphin), SLC8A3 (Na + -Ca 2+ exchanger), c-fos, HRK , and TNFAIP3 (TNF-α-induced protein 3, A20) (17, 1922).…”
Section: Dreammentioning
confidence: 99%
“…Studies using DREAM KO and Ca 2+ -insensitive/CRE binding(CREB)-independent dominant-active DREAM transgenic mice demonstrated that DREAM is involved in L-DOPA-induced dyskinesias and DREAM decreases L-DOPA-induced expression of FosB, dynorphin-B, and phosphoacetylated histone H3 in the striatum (39). Another study using the same transgenic mice suggested that the expression of dominant-active DREAM in the forebrain results in downregulation of Npas4, thereby reducing GABAergic inhibitory transmission and impairing learning and memory (18). Also, reduced DREAM expression in a transgenic mouse model of Huntington disease results in neuroprotection (40).…”
Section: Function Of Dreammentioning
confidence: 99%